Validation of the Questionnaire of the Transtheoretical Model of Change of Physical Exercise - Leyton, Marta (2019)
The aim of this study was to translate and validate in Spanish the Questionnaire of the Transtheoretical Model of Change of Physical Exercise, of Prochaska and DiClemente (1983), and also to make adaptations and modifications as needed. The sample was composed of 812 people, aged between 14 and 88 years (29.5+21.7) was used. Confirmative factorial analysis, analysis of internal consistency and of predictive validity were carried out. After the confirmative factorial analysis, the Questionnaire of the Theoretical Model of Change of Physical Exercise showed acceptable results (x2/g.1=4,3, CFI=0,92, IFI= 0.92, TLI = 0.90, RMSEA = 0.06, SRMR = 0,05). Similarly, internal consistency obtained from the respective dimensions showed values above .70. A positive and significant prediction of the most active stages of the Transtheoretical Model (action and maintenance) was found on the ‘intention to be physically active’. This study has enabled the provision of a valid and reliable.